(3Odjd VeGf GdLhOI hGdGYJeGO GdGcGOjej dHQGeL GdGYdGe hGdGJUGd GdLeGgjQj hab GdeYGjjQ GdOhdjI (BACEJMCs - (3ShSf TGcQ(B, (3eLjOs ((3YeGf(B:s (3OGQ TgQRGO ddfTQ hGdJhRjY(B,s, 2022)
(3eaGgje heUWdMGJ CSGSjI, eQGMd YedjI JWHjb Jbhje LhOI GdGOGA GdHQGeLj, NWhGJ GdMUhd Ydi TgGOI VeGf GdLhOI, eYGjjQ GYJeGO cdjGJ GdUMGaI hGdGJUGd GdLeGgjQj GdGeQjcjI, eYGjjQ heDTQGJ GdGYJeGO hGdGOdI, Gdbje hGdcaGAGJ GdegfjI, eYGjjQ GdMUhd Ydi GdGYJeGO GdHQGeLj aj eLGd GdUMGaI hGdGJUGd GdLeGgjQj ef bHd gjFI GdGYJeGO GdCeQjcjI (BACEJMC (3eYGjjQ GdMUhd Ydi TgGOI VeGf GdLhOI hGdGYJeGO dcdjGJ GdGYdGe hGdGJUGd ef GJMGO GdLGeYGJ GdYQHjI hab GWGQ gjFI GdGYJeGO GdCeQjcjI (BACEJMC(3, GdeDTQGJ GdfhYjI hGdcejI dcdjGJ GdGYdGe aj GdhWf GdYQHj aj GWGQ eYGjjQ GdGYJeGO GdGeQjcjI (B(ACEJMC)(3, GdCgOGa GdYGeI dcdjGJ GdGYdGe aj GdhWf GdYQHj, eYdheGJ YGeI Yf GdbSe GdOQGSj aj GdcdjI(B. s
Keywords: (3GdEYdGes; (3GdGYdGe hGdGJUGd GdLeGgjQjs; (3hSGFd GdEYdGes